A brief communication on the Top Ten Trends in the Hospitality Industry for 2024: World Scenario - Iyengar, M. Srividya; Venkatesh, Dr. R. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Technology plays an important role in the hotel industry now, and all indications suggest that it will continue to do so in the future. Hotels can now provide their guests with more customised and efficient experiences thanks to the ongoing advancement of technology. Hotels have used artificial intelligence to change how they connect with their clients, exceeding expectations and offering services and suggestions suited to their interests and preferences in an accurate and timely manner. Furthermore, the most recent AI apps have made it easier to communicate with visitors by using chatbots and virtual assistants that can answer frequently requested inquiries and deliver real-time information. On the other side, technology has had a favourable influence on hotel internal operations. Technology-based hotel management systems enable hotels to automate tasks like check-in and check-out, room management, and staff deployment. Hotels have improved operating efficiency, reduced expenses, and increased profitability by integrating cutting-edge technology. Where do hotel chains and tourist firms stand, what are the major issues they face after surviving the Covid-19 epidemic, how can they address these challenges, and how do they relate to technology? This brief report will give solution to all these questions.